PENGEMBANGAN METODE UJI SARING LIMA VARIETAS KACANG HIJAU (Vigna radiata) TAHAN KERING - Nafila Alifia Azka (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2021)
Mungbean (Vigna radiata) is one of the most widely cultivated legume in the world after soybeans and peanuts. Mungbean is easy to cultivate, but the facts in the field state that domestic mungbean production in Indonesia is still very low. One of the abiotic stress factors that often cause low mungbean production is drought, so it is necessary to develop a screening test method for five drought-resistant mungbean varieties, Kutilang (control/V1), Sriti (V2), Vima (V3), Murai ( V4), and Kenari (V5). Screening tests were carried out on the germination and vegetative phases using Polyethylene Glycol (PEG) 6000 with a dose of 0% PEG 6000 as control (K0), 5% PEG 6000 (K1), and 10% PEG 6000 (K2). Based on the results of the screening test of five mungbean varieties using PEG 6000, the germination phase was the most appropriate phase for a drought screening test. In the germination phase drought screening test, the varieties that were resistant to drought stress were Kenari, Sriti, Murai, and Vima, while those that were intolerant was Kutilang. In the vegetative phase, the most resistant variety was Kenari.